2012
DOI: 10.1111/j.2044-8295.2012.02105.x
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of study items in memory determines the magnitude and direction of directed forgetting

Abstract: When words at study are divided into to-be-remembered and to-be-forgotten ones, people recall more of the former than of the latter in a surprise memory test for all words. In this study, we also tapped memory for word identity at study (forget or remember) by asking participants to reproduce in memory selected portions of the original words. We found word identity to be parasitic on word reproduction. As a result, there is a noted tendency to recall forget-words from study as remember-words in the memory test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Earlier research (Ekstrand et al, 1966) has shown relative frequency to be a powerful mnemonic device. Our study reinforces its role in generating the PE (see more on the role of item segregation in memory in the recent study by Icht et al, 2013). …”
Section: Discussionsupporting
confidence: 90%
“…Earlier research (Ekstrand et al, 1966) has shown relative frequency to be a powerful mnemonic device. Our study reinforces its role in generating the PE (see more on the role of item segregation in memory in the recent study by Icht et al, 2013). …”
Section: Discussionsupporting
confidence: 90%